COMPARATIVE STUDY FOR EFFICACY OF DIFFERENT DIAGNOSTIC TESTS OF SUBCLINICAL MASTITIS IN GOATS IN TORO LOCAL GOVERNMENT AREA, BAUCHI STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2024)
This study was aimed to determine the comparative efficacy of various diagnostic tests for subclinical mastitis (SCM) in goats. The study was conducted on 210 (6 blind) quarter milk samples from 108 goats. Cultural examination was used as the gold standard to compare the accuracy of the following diagnostic tests: CMT, Masttest, Mastidin, Kerba test, Milk test, WST, BBST and SCC. The incidence rates were highest with CMT (28,7%) and lowest with Mastidin (22.2%). Cultivation revealed the presence of Coagulase-positive Staphylococcus, Coagulase-negative Staphylococcus, Streptococcus species, Bacillus species, Lactobacillus species, Escherichia coli, Salmonella species, Enterobacter species and Klebsiella species. No growth was observed on Brucella Agar. The sensitivity, specificity and predictive value of various tests were recorded and it was found that CMT had the highest sensitivity (32.89%), specificity (96.55%) and predictive value (96.15%) than compare with the other diagnostic methods for diagnosis of sub clinical mastitis in goat. The accuracy of all the conducted diagnostic tests when compared cultural examination were considered to be statistically significant (p
Keywords: Comparative efficacy; Diagnose; Subclinical mastitis; Goat; Test; Bacteria